Markets & Myths: Autonomy in Public & Private Schools - Glass, Sandra Rubin (Education Policy Analysis Archives, 1997)
School choice is the most controversial education policy issue of the 1990s. John Chubb and Terry Moe's Politics, Markets and America's Schools stimulated this investigation. They concluded that teacher and administrator autonomy was the most important influence on student achievement. They assumed that the organization of private schools offered greater autonomy resulting in higher student achievement and that the bureaucracy of public schools stifles autonomy limiting student achievement. The research undertaken here elaborates, elucidates, and fills in the framework of teacher and principal autonomy in public and private secondary schools. Interviews of more than thirty teachers and administrators in six high schools, observations, field notes, and analysis of documents collected in the field form the empirical base of this work. The sites included three private, independent, nondenominational secondary schools which are college preparatory and three public secondary schools noted for high graduation rates and offering numerous advanced placement courses. The feelings expressed by both public and private school participants in this study testify to equally high degrees of autonomy. Issues that emerged from data analysis in this study which mitigate and shape autonomy include the following: conflicting and contradictory demands, shared beliefs, layers of protection, a system of laws, funding constraints and matters of size of the institution. These issues challenge oversimplified assertions that differences of any importance exist between the autonomy experienced by professionals in public and private high schools. This study reveals the complexity of the concept of autonomy and challenges the myth that teachers and principals in private schools enjoy autonomy and freedom from democratic bureaucracy that their public school counterparts do not.